A Case Report of a Maxillary Second Molar with Two Distinct Palatal Canals, Confirmed by CBCT - Al-Qudah A; Afaneh A; Hassouneh L (Dove Medical Press, 2023)
Aladdin Al-Qudah, Asem Afaneh, Layla Hassouneh Department of Conservative Dentistry, Jordan University of Science and Technology, Irbid, JordanCorrespondence: Aladdin Al-Qudah, Department of Conservative Dentistry, Jordan University of Science and Technology, P.O. Box 3030, Irbid, 22110, Jordan, Email aqudah@just.edu.joAbstract: Cases of unusual and complex root canal morphology could be difficult to diagnose and treat. This report describes the diagnosis and management of a rare maxillary right second molar (tooth #17) with two distinct palatal canals. The tooth was diagnosed with irreversible pulpitis and symptomatic apical periodontitis. Non-surgical root canal treatment was performed. Accurate diagnosis and comprehensive treatment of cases with unusual root canal morphology can be achieved by evaluation of periapical radiographs at different angulations, advanced magnification techniques, and the Cone Beam Computed Tomography (CBCT) scanning. Clinicians should be aware that two separate palatal canals could exist in maxillary second molar teeth.Keywords: two palatal canals, root canal morphology, maxillary molar, cone beam computed tomography